Potential effect of different nutritional labels on food choices among mothers: a study protocol - Shirin Seyedhamzeh; Saharnaz Nedjat; Hedayat Hosseini; Elham Shakibazedeh; Anthony J. Viera; Ahmadreza Dorosty Motlagh (BMC, 2020)
Abstract Background The prevalence of non-communicable diseases (NCDs) is increasing in the world. Healthy food choice and adequate physical activity are key factors in preventing NCDs. Food labeling is a strategy that can inform consumers to choose healthier foods at the point of purchase. In this study, we intend to examine the status of existing labels and to clarify their strengths and weaknesses. Then, for the first time in Iran, we will design a type of physical activity equivalent calorie label and will test it on some food groups of packaged products including dairy products, sweetened beverages, cakes, and biscuits. Methods This study will be conducted in two phases. In phase 1, nutrition fact labels and traffic light labels will be assessed through focus group discussions and interviews among different groups of mothers, industrialists and nutrition and food industry specialists as to determine strengths and weaknesses of the current labels on packaged products. Then, the initial layout of the physical activity calorie equivalent label will be drawn with respect to the viewpoints received from mothers. Thereafter, we will include the scientific opinions to it for creating the first draft of our new label. In phase 2, a total of 500 mothers of students 6-12 years old randomly assigned to five groups. The study groups will be as follows: (1) without nutrition label group, (2) current traffic light label group, (3) current traffic light label group in which, a brochure will be used to inform mothers, (4) physical activity calorie equivalent label group, and (5) physical activity calorie equivalent label group in which a brochure will be used to inform mothers. Some samples of dairy products, beverages, cakes, and biscuits will be presented. ANOVA and multiple linear regressions will be used to examine the association between the label type and the main consequence (energy of the selected products) and secondary outcome (time). Discussion The effect of the new food labels will be evaluated based on the differences between the calories of selected food groups. Trial registeration Iranian Registery of Clinical Trials [IRCT]20,181,002,041,201 N1.